Ex vivo host and parasite response to antileishmanial drugs and immunomodulators. - Laura Gonzalez-Fajardo; Olga Lucía Fernández; Diane McMahon-Pratt; Nancy Gore Saravia (PLOS Neglected Tropical Diseases, 2015)
BACKGROUND:Therapeutic response in infectious disease involves host as well as microbial determinants. Because the immune and inflammatory response to Leishmania (Viannia) species defines the outcome of infection and efficacy of treatment, immunomodulation is considered a promising therapeutic strategy. However, since Leishmania infection and antileishmanial drugs can themselves modulate drug transport, metabolism and/or immune responses, immunotherapeutic approaches require integrated assessment of host and parasite responses. METHODOLOGY:To achieve an integrated assessment of current and innovative therapeutic strategies, we determined host and parasite responses to miltefosine and meglumine antimoniate alone and in combination with pentoxifylline or CpG 2006 in peripheral blood mononuclear cells (PBMCs) of cutaneous leishmaniasis patients. Parasite survival and secretion of TNF-α, IFN-γ, IL-10 and IL-13 were evaluated concomitantly in PBMCs infected with Luc-L. (V.) panamensis exposed to meglumine antimoniate (4, 8, 16, 32 and 64 μg SbV/mL) or miltefosine (2, 4, 8, 16 and 32 μM HePC). Concentrations of 4 μM of miltefosine and 8 μg SbV/mL were selected for evaluation in combination with immunomodulators based on the high but partial reduction of parasite burden by these antileishmanial concentrations without affecting cytokine secretion of infected PBMCs. Intracellular parasite survival was determined by luminometry and cytokine secretion measured by ELISA and multiplex assays. PRINCIPAL FINDINGS:Anti- and pro-inflammatory cytokines characteristic of L. (V.) panamensis infection were evaluable concomitantly with viability of Leishmania within monocyte-derived macrophages present in PBMC cultures. Both antileishmanial drugs reduced the parasite load of macrophages; miltefosine also suppressed IL-10 and IL-13 secretion in a dose dependent manner. Pentoxifylline did not affect parasite survival or alter antileishmanial effects of miltefosine or meglumine antimoniate. However, pentoxifylline diminished secretion ...